Role of Fibroblast Growth Factor 10 in Mesenchymal Cell Differentiation During Lung Development and Disease - Wu, Jin; Chu, Xuran; Chen, Chengshui; Bellusci, Saverio (Frontiers in Genetics, 2018)
During organogenesis and pathogenesis, fibroblast growth factor 10 (Fgf10) regulates mesenchymal cell differentiation in the lung. Different cell types reside in the developing lung mesenchyme. Lineage tracing in vivo was used to characterize these cells during development and disease. Fgf10-positive cells in the early lung mesenchyme differentiate into multiple lineages including smooth muscle cells (SMCs), lipofibroblasts (LIFs) as well as other cells, which still remain to be characterized. Fgf10 signaling has been reported to act both in an autocrine and paracrine fashion. Autocrine Fgf10 signaling is important for the differentiation of LIF progenitors. Interestingly, autocrine Fgf10 signaling also controls the differentiation of pre-adipocytes into mature adipocytes. As the mechanism of action of Fgf10 on adipocyte differentiation via the activation of peroxisome proliferator-activated receptor gamma (Pparγ) signaling is quite well established, this knowledge could be instrumental for identifying drugs capable of sustaining LIF differentiation in the context of lung injury. We propose that enhanced LIF differentiation could be associated with improved repair. On the other hand, paracrine signaling is considered to be critical for the differentiation of alveolar epithelial progenitors during development as well as for the maintenance of the alveolar type 2 (AT2) stem cells during homeostasis. Alveolar myofibroblasts (MYFs), which are another type of mesenchymal cells critical for the process of alveologenesis (the last phase of lung development) express high levels of Fgf10 and are also dependent for their formation on Fgf signaling. The characterization of the progenitors of alveolar MYFs as well the mechanisms involved in their differentiation is paramount as these cells are considered to be critical for lung regeneration. Finally, lineage tracing in the context of lung fibrosis demonstrated a reversible differentiation from LIF to “activated” MYF during fibrosis formation and resolution. FGF10 expression in the lungs of idiopathic pulmonary fibrosis (IPF) vs. donors as well as progressive vs. stable IPF patients supports our conclusion that FGF10 deficiency could be causative for IPF progression. The therapeutic application of recombinant human FGF10 is therefore very promising.